Improved metal-graphene contacts for low-noise, high-density microtransistor arrays for neural sensing. (May 2020) - Schaefer, Nathan; Garcia-Cortadella, Ramon; Calia, Andrea Bonaccini; Mavredakis, Nikolaos; Illa, Xavi; Masvidal-Codina, Eduard; Cruz, Jose de la; Corro, Elena del; Rodríguez, Laura; Prats-Alfonso, Elisabet; Bousquet, Jessica; Martínez-Aguilar, Javier; et al.
Abstract: Poor metal contact interfaces are one of the main limitations preventing unhampered access to the full potential of two-dimensional materials in electronics. Here we present graphene solution-gated field-effect-transistors (gSGFETs) with strongly improved linearity, homogeneity and sensitivity for small sensor sizes, resulting from ultraviolet ozone (UVO) contact treatment. The contribution of channel and contact region to the total device conductivity and flicker noise is explored experimentally and explained with a theoretical model. Finally, in-vitro recordings of flexible microelectrocorticography (μ-ECoG) probes were performed to validate the superior sensitivity of the UVO-treated gSGFET to brain-like activity. These results connote an important step towards the fabrication of high-density gSGFET μ-ECoG arrays with state-of-the-art sensitivity and homogeneity, thus demonstrating the potential of this technology as a versatile platform for the new generation of neural interfaces. Graphical abstract: Image 1